ANALISIS KEMAMPUAN MENULIS CERITA PENDEK PADA SISWA KELAS VI SD NEGERI CILUMBA I - Putri, Ade; Zahara Nurani, Riga; Nugraha, Fajar (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2025)
This study aims to assess the short story writing ability of grade VI students at Cilumba I Elementary School, with an emphasis on understanding the intrinsic elements of short stories, neatness of writing, and accuracy of spelling in accordance with EYD rules. The method used in this study is a descriptive qualitative approach, by collecting data through observation, interviews with class teachers, and analyzing the writings of six students selected based on high, medium, and low ability categories. The results of the study indicate that students’ understanding of the intrinsic elements of short stories, such as theme, plot, character, setting, message, point of view, and writing style, varies and has not been fully mastered by some students. In terms of neatness, there is a significant difference between students who have regular and structured writing and those who pay less attention to neatness. In addition, there are several errors in the application of spelling, such as errors in the use of capital letters, punctutation, and sentence structure. These findings indicate that the majority of students still need direction in writing short stories that are in accordance with the correct language structure and rules. The conclusion of this study emphasizes that the short story writing skills of grade VI students at Cilumba I Elementary School still need to be improved through a more focused and consistent learning process, especially in understanding intrinsic elements, neatness of writing, and the application of spelling in accordance with EYD rules.